Karakteristik Alterasi dan Mineralisasi Endapan Emas Tipe Carlin pada Blok Yance dan Leon, Kecamatan Ratatotok, Kabupaten Minahasa Tenggara, Provinsi Sulawesi Utara - Alyna Azarine; Muhammad Arba Azzaman; Arifudin Idrus (Universitas Muslim Indonesia, 2022)
Study of gold deposit in Mesel, Ratatotok, North Sulawesi has been conducted by numerous experts, but there has been no detailed research on other prospects near Mesel, like Yance and Leon where this study is conducted. The objectives of this study is to determine the differences in the characteristics of hydrothermal alteration and ore mineralization in the Yance and Leon Prospects. Core sample description, microscopic analyses (petrography, ore microscopy), X-Ray Diffraction, and SEM-EDX are the methods used to identify those characteristics. The results of these analyses indicate that limestone and collapse breccia controlled alteration and mineralization in this area. Hydrothermal alteration that are developed in this area are silicification, silica-calcite, illitesmectite- chlorite±calcite. Ore minerals are found as dissemination, replacement, and open-space fill, such as pyrite, arsenopyrite, realgar, orpiment, hematite, and goethite, with gangue minerals such as quartz, calcite, dolomite, gypsum, chlorite, kaolinite, illite, smectite, and rhomboclase. Analysis on mineral chemistry identify numerous elements, essentially Fe, S, As, Cu, Au, Ag, Sb, Cd, Co, and Ni where average Co content is higher than average Ni. The difference in characteristics between the two research sites is that the source rock of the Yance Block has limestone lithology and polymyctite breccia, while in the Leon Block the source rock is limestone. Alterations that have developed in the Yance Block include decalcification, silicification, silica-calcite, and illit-smectite-chlorite±calcite with replacement-type and open-space fillingmineralization, while in theLeon Block is silicification, silica-calcite. , and illite-smectite-chlorite±calcite with the dominant type of replacement mineralization. The ore minerals found in the Yance Block include pyrite, arsenopyrite, realgar, orpimen, hematite, goethite, while in the Leon Block they are pyrite and hematite.